Seasonal Prevalence of Major Mastitis Pathogens Isolated from Crossbred Cow Milk Samples in Sub-tropical India - Tiwari, Shiwani; Lathwal, S. S.; Devi, Indu; Tomar, Divyanshu Singh (Indian Journal of Animal Production and Management, 2024)
The dairy industry suffers significant financial losses due to mastitis. In order to control and prevent mastitis, it is imperative to continuously monitor the bacteriology, prevalence, and incidence of major mastitis pathogens. Thus, the objective of this research was to find out how often mastitis-causing bacteria were isolated from milk samples of crossbred cows over various seasons in India's sub-tropical environment. 240 milk samples from 80 different cows were collected over the course of three seasons [Hot Dry (April to June), Hot Humid (July to September), and Autumn (October to November)] in order to correlate the prevalence of four main mastitis pathogens (Staphylococcus aureus, Streptococcus agalactiae, Streptococcus dysgalactiae, and Escherichia coli) with the season. The most prevalent isolate during all seasons was Staphylococcus aureus. Our findings demonstrated a discernible relationship between seasonal change and the isolation rate of the bacterium associated with bovine mastitis, with the hot-humid season having the greatest pathogen isolation rate